Transfer pricing and corporate social responsibility: Arguments, views and agenda - Simplice Asongu; Joseph I. Uduji; Elda N. Okolo-Obasi (African Governance and Development Institute (AGDI), 2019)
The central thesis of the paper is that Multinational Companies (MNC) should invest in the use of "soft" methods (socially responsible behavior) to mitigate costs in society accrued due to use of "hardcore" tax evasion tactics (Transfer mispricing) to maximize profits from operations in developing countries and/or countries with weak or inefficient tax laws and tax collection institutions. Therefore, we articulate the argument of Corporate Social Responsibility (CSR) as an indirect compensation for transfer mispricing. Our aim is not to present CSR as solution to transfer mispricing. An analytical approach is based on a content analysis of the existing literature with emphasis on a case study. We first discuss the dark side of transfer pricing (TP), next we present the link between TP and poverty and finally we advance arguments for CSR as a compensation for transfer mispricing. While acknowledging that TP is a legal accounting practice, we argue that in light of its poverty and underdevelopment externalities, the practice per se should be a strong defence for CSR because it is also associated with schemes that deprive developing countries of the capital essential for investment in health, education and development programmes.
Keywords: F20; H20; M14; O11; 330; Corporate Social Responsibility; Transfer pricing; Extreme poverty